Critical factors influencing green consumer behavior: A case study in Vietnam (Journal of Social Economics Research, 2024)
Green shopping is becoming increasingly popular as a way of saving the environment and combating climate change in Vietnam and many other nations across the world. In addition, the agriculture sector, along with other industries such as manufacturing, services, commerce, and environmentally conscious consumption, is being examined in the global shift towards sustainable green consumption. This is in line with attempts to adopt eco-friendly solutions and mitigate climate change. As a result, the study investigated the critical elements influencing individual consumers' green consumer behavior in five Vietnamese provinces and gave management recommendations for improving green consumer behavior. The article technique utilized structural equation modeling (SEM), the statistical package for the social sciences (SPSS), and Amos. In addition, data was collected from 700 green product buyers. The findings of the article identified five essential factors influencing green consumer behavior: green products, the price of green products, green places, green promotion, and green policy. The article provides valuable insights for managers to develop an effective green marketing plan for businesses that sell organic food products. The goal is to encourage customers to embrace environmental consciousness and promote sustainable development. Additionally, the article emphasizes the importance of conveying positive information about green businesses. The value of this study raises awareness of the fact that green consumption is a comprehensive and responsible management process that satisfies, identifies, meets, and predicts the needs of producers, sellers, and consumers while preserving the natural health of the environment and not endangering human health.